IEEE Symposium Conference Record Nuclear Science 2004.
DOI: 10.1109/nssmic.2004.1462616
|View full text |Cite
|
Sign up to set email alerts
|

The MAGIC-5 project: medical applications on a grid infrastructure connection

Abstract: The MAGIC-5 Project aims at developing Computer Aided Detection (CAD) software for Medical Applications on distributed databases by means of a GRID Infrastructure Connection. The use of automatic systems for analyzing medical images is of paramount importance in the screening programs, due to the huge amount of data to check. Examples are: mammographies for breast cancer detection, Computed-Tomography (CT) images for lung cancer analysis, and the Positron Emission Tomography (PET) imaging for the early diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 3 publications
0
21
1
Order By: Relevance
“…Even though this global percentage was not optimal, it represents an interesting point for future investigation, since it contradicts other studies which concluded that microcalcification are a more predictable lesion than masses (36,54). We can conclude that, for the scenario 3, in distinguishing the type of mammographic lesion the best performance was obtained for scenario 3a by the use of k-NN classifier and for Random Forest classifier in scenario 3b.…”
Section: Chapter 6 Conclusion and Further Workcontrasting
confidence: 58%
“…Even though this global percentage was not optimal, it represents an interesting point for future investigation, since it contradicts other studies which concluded that microcalcification are a more predictable lesion than masses (36,54). We can conclude that, for the scenario 3, in distinguishing the type of mammographic lesion the best performance was obtained for scenario 3a by the use of k-NN classifier and for Random Forest classifier in scenario 3b.…”
Section: Chapter 6 Conclusion and Further Workcontrasting
confidence: 58%
“…In the state-of-the-art, there are a number of works that make use of predictive models or radiomic analysis to identify and characterize breast neoplasms and the state of lymph node involvement [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magic 5 [9] uses distributed computing infrastructure (GRID) to increase computational speed and accessibility, and share distributed image databases and aims at diagnosing early detection of lung cancer.…”
Section: Performance Evaluationmentioning
confidence: 99%